2013
DOI: 10.7243/2052-4358-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Pericardiectomy for constrictive pericarditis with postoperative increase of tricuspid regurgitation

Abstract: We report a case of tricuspid regurgitation (TR) that increased markedly after pericardiectomy for constrictive pericarditis. Preoperative mild-to-moderate TR increased to severe following surgery. The patient was asymptomatic, and gradual regression of TR was observed. Eighteen months postoperatively, a left atrial thrombus formed, and a second surgery consisting of thrombectomy and tricuspid annuloplasty was performed. The increase in TR after pericardiectomy was thought to be due to dilatation of the right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…TR worsened after the operation in both groups, but it was aggravated more in the conventional group in the last echocardiography. Several cases of worsening TR or right ventricular dysfunction after pericardiectomy have been reported [2325]. Mantri et al concluded if an adequate pericardiectomy is done at an earlier stage, the regurgitations will regress [26].…”
Section: Discussionmentioning
confidence: 99%
“…TR worsened after the operation in both groups, but it was aggravated more in the conventional group in the last echocardiography. Several cases of worsening TR or right ventricular dysfunction after pericardiectomy have been reported [2325]. Mantri et al concluded if an adequate pericardiectomy is done at an earlier stage, the regurgitations will regress [26].…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Pericardial calcification can be noticed, which is found on the inferior and diaphragmatic surface in 97%, on the anterior RV surface area in 76%, and on the left atrioventricular groove in 62%. 2,12,13 Magnetic resonance techniques reveal lack of pericardial slippage (adherence). The combination of pericardial non-slippage and ventricular interdependencies suggests constrictive pericarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of poor outcome after pericardiectomy are New York Heart Association class IV, myocardial fibrosis, underlying malignancy, radiation-induced myocardial inflammation with scarring, and previous pericardial surgery. 2,6,13,14 Of late, an ultrasonic scalpel with a hook-type blade has been utilized for pericardiectomy. With no hyperthermic damage, no myocardial stimulation, minimal strokes, and good hemostasis, pericardiectomy is performed using longitudinal vibration (55,500/s) and cavitational fragmentation that disrupts low-density tissue.…”
Section: Discussionmentioning
confidence: 99%
“…There are several case reports of postoperative increase of TR [1,11]. Johnson TL, et al reported two cases of postoperative TR increase in 1993 [11].…”
Section: Increase In Tr Following Operation Without Tricuspid Valve I...mentioning
confidence: 99%
“…In 2013, the author (Taguchi S) published a case of conventional pericardiectomy for constrictive pericarditis [1]. In this case, preoperative mild-moderate tricuspid regurgitation (TR) worsened as severe postoperatively.…”
Section: Introductionmentioning
confidence: 99%